Risk factors for post-traumatic osteoarthritis and subsequent total hip arthroplasty in patients with acetabular fractures - Hung Yen Chen; Yao Hung Tsai (BMC Musculoskeletal Disorders)
Abstract Background Post-traumatic osteoarthritis (PTOA) often develops after acetabular fractures, leading to a need for total hip arthroplasty (THA). This study aimed to identify the risk factors associated with PTOA and subsequent THA among patients with acetabular fractures treated with open reduction and internal fixation (ORIF). Methods The records of patients with closed acetabular fractures treated at a tertiary care medical center in Taiwan from 2002 to 2019 were retrospectively reviewed. Eligibility criteria were patients who underwent ORIF with a minimum follow-up of 2 years. The primary outcomes were occurrence of PTOA and subsequent THA. Multivariate logistic regression was employed to identify significant factors associated with PTOA and THA. Results A total of 54 patients were included, with a mean age of 41.4 years and 76% were male (n = 41). PTOA occurred in 28 patients (52%), and 13 patients (24%) required THA. Advanced age (adjusted odds ratio [aOR] = 1.05, 95% confidence interval [CI]: 1.00-1.10, p = 0.035) and a both column fracture (aOR = 12.80, 95% CI: 2.21–74.16, p = 0.004) were significant predictors of PTOA. Time to ORIF (aOR = 1.36, 95% CI: 1.06–1.75, p = 0.018) and unsatisfactory Matta criteria (aOR = 7.62, 95% CI: 1.30-44.58, p = 0.024) were significant predictors for subsequent THA. Conclusion Age and fracture pattern are independent predictors of PTOA, while time to ORIF and Matta criteria are predictive of the need for THA. Early timing of ORIF could decrease the likelihood of subsequent THA, underscoring the importance of prompt surgical intervention in clinical decision-making to optimize patient outcomes. Further research is needed to refine preoperative risk stratification and clinical management strategies for patients with acetabular fractures.